Analysis of Neutrophil Lymphocyte Ratio and Absolute Lymphocyte Count as Predictors of Severity of COVID-19 Patients - Yunianingsih Selanno; Yuyun Widaningsih; Tenri Esa; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
It is important to predict the severity of COVID-19 during the pandemic. Both Neutrophil Lymphocyte Ratio (NLR) and Absolute Lymphocyte Count (ALC) are two easy, low-cost, and fast inflammatory markers, which positively correlate with the severity of COVID-19. The purpose of this research was to analyze the value of NLR and ALC as predictors of COVID-19 severity. This research was a retrospective study using medical record data of 376 COVID-19 patients during April-September 2020 at the Hasanuddin University Hospital and Makassar City Regional Hospital. Patients were classified into non-severe and severe COVID-19. Neutrophil lymphocyte ratio and ALC values were determined based on routine blood test (Sysmex XS-800i) results, statistical analysis using Independent T-test, while NLR and ALC diagnostic values were analyzed with Receiver Operating Characteristics (ROC) curve to obtain the cut-off value, p < 0.05 was significant. The samples consisted of 372 non-severe and 49 severe COVID-19 patients. Neutrophil lymphocyte ratio value in non-severe (4.02±5.22) was significantly different from severe COVID-19 (9.81±7.06) (p < 0.001), similar to ALC in non-severe (2.00±0.83x103/Î¼L) and severe COVID-19 (1.22±0.78x103/Î¼L) (p < 0.001). Receiver operating characteristics curve showed that NLR had a sensitivity of 91.8% and specificity of 66.4% with a cut-off â‰¥ 3.17 with Negative Predict Value (NPV) of 98.2% and Positive Predict Value (PPV) of 29.0%; while ALC had a sensitivity of 81.6% and specificity of 64.8% at cut-off â‰¤ 1.74x103/Î¼L with NPV of 95.9% and PPV of 25.8%. Increased NLR and decreased ALC in severe COVID-19 patients occurred due to an increased inflammatory response resulting in a decreased cellular immunity. Receiver operating characteristics curve showed a cut-off for NLR of 3.17 and ALC of 1.74x103/Î¼L, indicating an optimum sensitivity and specificity. It was concluded that NLR and ALC can be used as predictors of COVID-19 severity with a cut-off â‰¥ 3.17 and â‰¤ 1.74x103/Î¼L, respectively.